Incidence of Concurrent Peroneal Nerve Injury in Multiligament Knee Injuries and Outcomes after Knee Reconstruction - Worley, John R.; Brimmo, Olubusola; Nuelle, Clayton W.; Cook, James L.; Stannard, James P. (The Journal of Knee Surgery, 2019)
The purpose of this study was to determine incidence of concurrent peroneal nerve injury and to compare outcomes in patients with and without peroneal nerve injury after surgical treatment for multiligament knee injuries (MLKIs). A retrospective study of 357 MLKIs was conducted. Patients with two or more knee ligaments requiring surgical reconstruction were included. Mean follow-up was 35 months (0–117). Incidence of concurrent peroneal nerve injury was noted and patients with and without nerve injury were evaluated for outcomes. Concurrent peroneal nerve injury occurred in 68 patients (19%). In patients with nerve injury, 45 (73%) returned to full duty at work; 193 (81%) patients without nerve injury returned to full duty (p = 0.06). In patients with nerve injury, 37 (60%) returned to their previous level of activity; 148 (62%) patients without nerve injury returned to their previous level of activity (p = 0.41). At final follow-up, there were no significant differences in level of pain (mean visual analog scale 1.6 vs. 2; p = 0.17), Lysholm score (mean 88.6 vs. 88.8; p = 0.94), or International Knee Documentation Committee score (mean 46.2 vs. 47.8; p = 0.67) for patients with or without peroneal nerve injury, respectively. Postoperative range of motion (ROM) (mean 121 degrees) was significantly lower (p = 0.02) for patients with nerve injury compared with patients without nerve injury (mean 127 degrees). Concurrent peroneal nerve injury occurred in 19% of patients in this large cohort suffering MLKIs. After knee reconstruction surgery, patients with concurrent peroneal nerve injuries had significantly lower knee ROM and trended toward a lower rate of return to work. However, outcomes with respect to activity level, pain, and function were not significantly different between the two groups. This study contributes to our understanding of patient outcomes in patients with concurrent MLKI and peroneal nerve injury, with a focus on the patient's ability to return to work and sporting activity.
Keywords: multiligament knee injuries; peroneal nerve injury; range of motion; return to work; return to activity